Gender and sex differences in job status and hypertension. Issue 1 (23rd September 2010) - Clougherty, Jane E; Eisen, Ellen A; Slade, Martin D; Kawachi, Ichiro; Cullen, Mark R
Abstract : Objectives: Studies have shown greater health risks associated with blue-collar manufacturing employment for women than men. It remains challenging, however, to distinguish gendered job status (affected by family composition and other personal characteristics) from sex-linked biological differences influencing physiological response to workplace physical hazards. Methods: We examined the effects of hourly (blue-collar) status on incident hypertension among men and women, using health claims data for 14 618 white- and blue-collar aluminium manufacturing employees in eight US states. To explore gender differences in job status, we developed sex-stratified propensity score models identifying key socioeconomic predictors of hourly status for men and women. To examine the effects of hourly employment on hypertension risk, after adjusting for gender differences in job status, we applied time-weighted logistic regression models, stratified by propensity score, with additional adjustment for socioeconomic confounders. Results: Family structure (partnership, parity) influenced job status for both sexes; single mothers were more likely to hold hourly jobs (OR 2.02; 95% CI 1.37 to 2.97) and partnered men with children less likely (OR 0.68; 95% CI 0.56 to 0.83). Education, age at hire and race influenced job status for both sexes. The effect of hourly status on hypertension was significant only among women predicted to be hourly (OR 1.78; 95% CI 1.34 to 2.35). Conclusions: Our results indicate significant risks of hypertension associated with hourly status for women, possibly exacerbated by sociodemographic factors predicting hourly status (eg, single parenthood, low education). Greater attention to gender differences in job status, and finer exploration of sex-linked biological differences influencing responsivity to workplace exposures, is warranted.